Analysis Of Violations Of The Maxim Of Cooperation In The Youtube Channel Of Lost Youth (Buying Cheetahs So That Then The End Will Ride Cheetahs): A Pragmatic Study - Hidayatul Khasanah; Syahranie Mulya Winanti; Desy Prasetyaningsih; Eva Setyorini; Asep Purwo Yudi Utomo; Eva Wulandari; Rossi Galih Kesuma (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The principle of cooperation is definitely needed in a conversation, because with this principle, speakers and interlocutors can communicate cooperatively. Apart from helping speakers and speech partners achieve common goals in conversation, the maxim of cooperation can also provide a framework for communication to be more efficient and effective, so that it can benefit speakers and speech partners. However, sometimes in a conversation, violations arise from the speaker or speech partner involved and result in a violation of the principle of cooperation. Violations in the principle of cooperation in a speech can cause information defects and give rise to disagreements between the speaker and the speech partner. Therefore, this research was carried out with the aim of determining and explaining the types of violations of the principle of cooperation in conversations on the content of Lost Youth: